Morphology and Phylogenomics serving protection of biodiversity : systematics of Dombeya section Dombeya (Malvaceae). - (:unkn) unknown (My University, 2023)
The Dombeya Cav. genus (Malvaceae, ex-Sterculiaceae) comprises around 150 emblematic species from the western Indian Ocean. This genus is found in Africa, the Comoros, the Mascarenes and in many habitats of Madagascar; in each of these areas of distribution, Dombeya has a specific endemism rate of almost 100%. This ecological and specific diversity seems to be linked to major morphological variations and original life-history traits. With an estimated age of less than 10 Ma, this specific diversity and morpho-ecological complexity could be the result of rapid radiation. The taxonomy of the genus is still debated and still requires major taxonomic revision.Our study is part of this approach and focuses on a particular section of the genus: the autonymic section Dombeya, which occurs in all the genus' distribution areas. The section is characterised by a unique feature within the subfamily: a biparous cyme inflorescence with scorpioid terminal units. Using morphometric, morphological and genetic approaches, we were able to test species hypotheses previously formulated in the literature. The floral organs have proved to be a good object of biological study for differentiating taxonomic entities: three major geographical groups, African, Madagascan and Mascarenan, have thus been defined. A molecular approach using genome skimming was then used to extract the largest molecular matrix produced in the genus, which was used for phylogenetic analyses. By combining morphometry, a global morphology approach and phylogeny at the section level, two distinct taxonomic entities emerged within Dombeya sect. Dombeya. The monophyly of the section is not confirmed and it seems that the scorpioid biparous cyme character was acquired twice independently in Africa and Madagascar. The Malagasy species appear to be closely related to the Mascarenan species, which are thought to have derived from them, and form at least 3 distinct taxonomic units, the delimitation of which is
Keywords: African Research